الأنشطة الحرفية بالمنطقة المغاربية مع بداية العصر الحديث: معلومات حول المقال: تاريخ الاستلام 2022-12-04 —– تاريخ القبول 14-01-2025 - قدوري عبد الرحمن; كبداني فؤاد (مجلة الآداب و العلوم الإجتماعية, 2025)
Craft activities in the Maghreb countries increased at the beginning of the modern era, and they played an important role in stimulating commercial life, and also established the emergence of large cities of a certain industrial character, such as west Tripoli, Tunis, Algiers , Oran, Tlemcen, Fez and Marrakech, What really contributed to this development is the abundance of raw materials and the diversity of the social structure in addition to the strategic location between Europe and Africa beyond the desert and the Arab East.That is why many activities and crafts arose, among them the textile industry, whose materials were available, which resulted in a great internal and external demand for it, in addition to the activity of blacksmithing, pottery, copper, leather, and food industries. As for the manufacture of ships and weapons, it has flourished due to the availability ofthe main materials such as wood and iron, in addition to the encouragement of the Maghreb rulers of this type of industry.Thesecrafts had their own organizations, one each trade had a specific group that practiced it and specialized in it, and had a hierarchical organization headed by the Secretary, who is the first responsible official, and in this organization were all the makers and apprentices, thus each specific group had its own craft according to the diversity of the population :Maghrebis,Andalusians, Jews and Christians